Pemanfaatan Media Digital Marketing pada Usaha Keripik Pisang di Desa Ledokombo, Jember - Agus Supriono; Riza Oktafiyani; Ariq Dewi Maharani; Tiffany Rahma Abdillah; Soetriono Soetriono; Yuli Hariyati; Anik Suwandari (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
The banana chip business in Ledokombo Village, Jember Regency, is one of the sources of livelihood for the local community. However, increasingly fierce business competition has led to a decrease in demand and has an impact on declining turnover of MSME actors. Marketing that is still conventional is one of the factors limiting product reach. This community service activity aims to increase the marketing capacity of MSME actors through digital marketing training. The training was carried out for four weeks with stages: problem analysis, provision of branding and digital marketing materials, assistance in making packaging labels, marketplace accounts (Shopee) and social media (Instagram), as well as monitoring and evaluation. The results of the activity show that MSME actors understand the importance of digital marketing strategies, are able to create